2019
DOI: 10.3892/mmr.2019.10551
|View full text |Cite
|
Sign up to set email alerts
|

Berberine ameliorates CCl4‑induced liver injury in rats through regulation of the Nrf2‑Keap1‑ARE and p53 signaling pathways

Abstract: Berberine (BBR) is an isoquinoline alkaloid, reported to have multiple pharmacological functions. However, its effects against CCl4-induced oxidative damage remain poorly studied. Therefore, the present study investigated the protective action of BBR, and its antioxidant mechanisms, against CCl4-induced liver injury in rats. A total of 48 rats were randomly arranged into six groups: Control; model; positive control (PC); BBR low-dose (BL); BBR middle-dose (BM); and BBR high-dose (BH). The BL, BM and BH animals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 27 publications
4
15
0
Order By: Relevance
“…Moreover, the decline of GSH and SOD levels was reportedly due to ROS release in the CCl 4 mouse model of encephalopathy 29 . The dysregulated antioxidant mechanism in the current model was in line with previous reports 1,30 , in which an elevated MDA and reduced antioxidant mechanism in different brain regions were observed following CCl 4 intoxication. MOLE pretreatment successfully restored the antioxidative power in HC and CC through the reduction of MDA and restoration of antioxidative mechanisms which was in agreement with Idoga et al, (2018) 31 .…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the decline of GSH and SOD levels was reportedly due to ROS release in the CCl 4 mouse model of encephalopathy 29 . The dysregulated antioxidant mechanism in the current model was in line with previous reports 1,30 , in which an elevated MDA and reduced antioxidant mechanism in different brain regions were observed following CCl 4 intoxication. MOLE pretreatment successfully restored the antioxidative power in HC and CC through the reduction of MDA and restoration of antioxidative mechanisms which was in agreement with Idoga et al, (2018) 31 .…”
Section: Discussionsupporting
confidence: 92%
“…These results are in agreement with the biochemical results where CCl 4 administration caused a significant elevation in MDA and NO levels beside GSR activity, with significant declines in GSH level and the activities of SOD, t-GPx and GST as compared to the control group. This indicates that CCl 4 induced OS where it increased LP and disrupted the antioxidant system in the liver [ 56 , 57 ]. In the liver, CCl 4 is bio-transformed into active metabolites (CCl 3 • and CCl 3 OO•) which are responsible for the increment of the MDA level through the enhancement of LP of the polyunsaturated fatty acids of the cell membrane [ 58 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…6 ” indicating that CCl 4 induces hepatocytes apoptosis. Where, p53 triggers the apoptosis by increasing the pro-apoptotic gene expression and decreasing the anti-apoptotic genes [ 57 , 75 ]. Previous studies reported that the promoter of the p53 gene has different binding sites one of them for p53 itself and another one for NF-κB since, the activation of NF-κB lead to up-regulation of p53 gene expression [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pretreatment with quercetin further activates the Keap1/Nrf2/ARE-anti-oxidant pathway, which induces cellular defenses against various oxidative stress [128]. Recent reports have shown that p53 can activate the Keap1/Nrf2/ARE-anti-oxidant pathway and can act as the main regulator of the cells anti-oxidant response [129,130]. This effect of p53 largely depends on the intensity and degree of oxidative stress imposed.…”
Section: Quercetinmentioning
confidence: 99%